2020
DOI: 10.1111/epi.16769
|View full text |Cite
|
Sign up to set email alerts
|

Brivaracetam as add‐on treatment in focal epilepsy: A real‐world time‐based analysis

Abstract: The study assessed the clinical response to add‐on brivaracetam (BRV) in real‐world practice by means of time‐to‐baseline seizure count methodology. Patients with focal epilepsy who were prescribed add‐on BRV were identified. Primary endpoint was the time‐to‐baseline seizure count defined as the number of days until each patient experienced the number of focal seizures that occurred in the 90 days before BRV initiation. Subgroup analysis was performed according to levetiracetam (LEV) status (naive vs prior use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 20 publications
4
15
0
Order By: Relevance
“…Patients had a history of a median of 5 [3][4][5][6][7][8] lifetime ASMs, and BRV was added to a median of 2 [1][2][3] concomitant ASMs; the most common concomitant ASMs were carbamazepine, valproic acid and lacosamide. The median baseline seizure frequency was 5 [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18], and 35 (3.4%) patients were seizure-free during the 3 months before starting BRV. The baseline characteristics of participants are summarized in Table 1 and details about the concomitant ASMs are shown in Table 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients had a history of a median of 5 [3][4][5][6][7][8] lifetime ASMs, and BRV was added to a median of 2 [1][2][3] concomitant ASMs; the most common concomitant ASMs were carbamazepine, valproic acid and lacosamide. The median baseline seizure frequency was 5 [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18], and 35 (3.4%) patients were seizure-free during the 3 months before starting BRV. The baseline characteristics of participants are summarized in Table 1 and details about the concomitant ASMs are shown in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Simple and multivariable logistic regression models were performed to identify baseline characteristics of patients associated with 12-month seizure freedom. Preselected independent variables were age, sex, number of previous ASMs, number of concomitant ASMs, baseline monthly seizure frequency, and LEV status [16][17][18]; age, number of previous ASMs, number of concomitant ASMs, and baseline monthly seizure frequency were entered into regression models as continuous variables, and sex and LEV status as categorical variables.…”
Section: Discussionmentioning
confidence: 99%
“…44 As previously reported, the lack of efficacy was the most commonly reported reason for BRV treatment discontinuation. 40 Several limitations of this study should be acknowledged. First, this study is limited by the risks inherent to any study with a retrospective design, including the potential for relevant information to be missing from records, the lack of randomization, and variations in follow-up timing.…”
Section: Discussionmentioning
confidence: 92%
“…Previous data suggest that BRV is effective and well tolerated in patients switched from LEV. 40,41 The reduced efficacy observed after 3 months in patients switched from LEV might be due to the BRV target dose being initiated almost immediately in those with previous LEV treatment, whereas those patients who were not switched from LEV were introduced to BRV using a slow titration period. Nonresponders might also be distinguished earlier among patients who switch from LEV compared with those without previous LEV treatment.…”
Section: Discussionmentioning
confidence: 99%
“…BRV brivaracetam, CNB cenobamate, CI confidence interval, ESL eslicarbazepine acetate, LCM lacosamide, PBO placebo, PER perampanel, SUCRA surface under the cumulative ranking curve on the actual effect of the treatment on the quality of life of patients. Further, the reliability of seizure count, as documented in clinical trials by self-reported calendar diaries, may be affected by issues like noncompliance with diary maintenance, poor accuracy in reporting, and limited awareness of seizures [57,58]. Accordingly, studies considering patient-reported outcomes and new approaches for collecting reliable information about seizure control are warranted to fully assess the potential of treatments in the management of patients with epilepsy.…”
Section: Strengths and Limitationsmentioning
confidence: 99%